IT Service management in multinational organizations: Contingency factors in the degree of federalization - Castro, Rui (2013)
Today, IT Service management is an important activity within organizations and it's becoming a particularly complex challenge for multinational companies due to specificities related with cultural and regional differences where the operations are located. This study seeks to identify which factors influence the adoption of IT Management models, namely the position in the centralization-decentralization continuum with particular importance in a multinational context. The performed research, based in a case study of a multinational industry with headquarters in Portugal, aims to validate theoretical IT organizational models and build a contingency factor reference, adjusted to a multinational scenario.